MODEL PENGELOLAAN PEMBUKAAN LAHAN TANPA BAKAR PADA USAHATANI PADI DIKABUPATEN SANGGAU - Noviyanti, Rizky; Yurisinthae, Erlinda; Suyatno, Adi (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2020)
The number of hotspots in West Kalimantan in 2018 was 1,075 hotspots. The highest hotspot in West Kalimantan is in Sanggau district which has 200 hotspots on August 15-16, 2018. This study aims to analyze the management model of land clearing without burning carried out by farmers in Sanggau District and determine the factors that have a tendency of farmers to choose the method cultivate land. The sampling method is a method of sampling the probability of 100 respondents calculated using the Slovin formula. Variable characteristics of farmers are age, education, farming experience, farmer knowledge and counseling. The analysis used is binary logistic regression analysis. Data collection was carried out through a questionnaire with direct interview techniques to farmers. The results showed that the factors that have the tendency of farmers to choose how to cultivate land are the age factor of farmers who have a significant value of 0.007 and the experience of farming that has a significant value of 0.034. This informs that the age variable is relatively high and relatively low farming experience has a tendency for farmers to choose how to cultivate land.